Pengaruh Pengendalian Internal, Whistleblowing System Dan Moralitas Individu Terhadap Pencegahan Kecurangan (Fraud) Pada LPD Se-Kecamatan Ubud - Lestari, Ni Putu Juni; Wati, Ni Wayan Alit Erlina; Pratiwi, Ni Putu Trisna Windika (Hita Akuntansi dan Keuangan, 2025)
Accounting knowledge plays a crucial role in the effective management of LPD funds. However, there is also the potential for misuse of this knowledge, leading to issues such as fraud. This study aims to investigate the impact of internal control, whistleblowing systems, and individual morality on fraud prevention within LPDs in the Ubud District. The study's population consists of all LPD employees in the Ubud District, comprising 378 employees across 30 LPDs. Data was collected from all 378 employees using a saturated sampling technique. The analysis methods employed include multiple linear regression, the coefficient of determination, as well as t-tests and F-tests. The results show that internal control systems, whistleblowing mechanisms, and personal ethical standards each contribute positively and significantly to the prevention of fraud.